Paracoccidioidomycosis - Franco, Marcello [UNESP]; da Silva Lacaz, Carlos; Restrepo-Moreno, Angela; Del Negro, Gildo (Taylor & Francis, 2018)
Paracoccidioidomycosis continues to be a serious health problem among rural workers in many Latin American countries. This deep mycosis has many similarities to other deep mycoses that affect the developed world. Furthermore, P. brasiliensis is becoming an excellent tool for basic studies (e.g., dimorphism, hormone-mediated host interactions, ecology). Paracoccidioidomycosis is an important publication with 30 chapters covering every aspect of the disease from its etiological agent, P. brasiliensis, to the clinical manifestations and treatment. The chapters are written by 45 specialists, each one a leading figure in his or her area of research. This reference is the first of its kind to be written in English. The book is a valuable addition to the reference collections of basic researchers and applied mycologists, as well as clinicians and others working with infectious and tropical diseases. It can also be used for courses on medical mycology.